2017
DOI: 10.1002/jcb.26319
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end‐products and Porphyromonas gingivalis lipopolysaccharide increase calprotectin expression in human gingival epithelial cells

Abstract: Accumulation of advanced glycation end-products (AGEs) in periodontal tissues of patients with diabetes mellitus aggravates periodontitis, but the mechanisms are unknown. Calprotectin, a heterocomplex of S100A8 and S100A9 proteins, is a constitutive cytoplasmic component of healthy gingival epithelial cells. This study aimed at investigating the effects of AGE and Porphyromonas gingivalis lipopolysaccharide (PgLPS) on calprotectin expression in the human gingival epithelial cell line OBA-9. AGE and PgLPS incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Furthermore, in the same study, with stimulation of AGE and/or P-LPS, the CLP complex was expressed not only in the cytoplasm but also in the nucleus. This result suggests that CLP might inhibit the growth of accelerated cells mediated by AGE and/or P-LPS by supporting repair of damaged tissues, thus maintaining the function of gingival epithelial barrier to resist infection and inflammation [87]. The findings mentioned above suggest that released CLP may act on periodontopathic bacteria in the presence of neutrophils and monocytes, but in the case of epithelial and keratinocytes, intracellular CLP may act on bacteria invading gingival epithelium.…”
Section: The Role Of Clp In Pdmentioning
confidence: 99%
“…Furthermore, in the same study, with stimulation of AGE and/or P-LPS, the CLP complex was expressed not only in the cytoplasm but also in the nucleus. This result suggests that CLP might inhibit the growth of accelerated cells mediated by AGE and/or P-LPS by supporting repair of damaged tissues, thus maintaining the function of gingival epithelial barrier to resist infection and inflammation [87]. The findings mentioned above suggest that released CLP may act on periodontopathic bacteria in the presence of neutrophils and monocytes, but in the case of epithelial and keratinocytes, intracellular CLP may act on bacteria invading gingival epithelium.…”
Section: The Role Of Clp In Pdmentioning
confidence: 99%
“…Liu et al have recently reported that bacterial LPS inhibits osteoblastic differentiation and alkaline phosphatase (ALP) activity by suppressing the expressions of osteocalcin, Runx2, and ALP, and then downregulates bone matrix mineralization [10]. Moreover, LPS induces inflammatory cytokine levels, such as IL-1β, IL-6, IL-8, TNF-α, and S100A8/S100A9 from various cells in periodontal tissues [11][12][13]. In a recent study, high levels of calprotectin were detected in gingival crevicular fluid (GCF) from patients with periodontitis, and high levels of S100A8 and S100A9 were also detected in blood vessels in Pg-infected mice [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the neutrophils in diabetic mice produced more inflammatory cytokines, chemokines, superoxide, and an increase in neutrophil rolling and attachment on the vascular wall of gingival tissue was observed in vivo, 10 suggesting that the higher GCF level of calprotectin in DM‐P patients might also be due to the hyperinflammatory phenotype of neutrophil under high glucose environment. Besides, recent evidence has revealed that advanced glycation end products (AGEs) generated by chronic hyperglycemia up‐regulate the expression of S100A8 and S100A9 in a human gingival epithelial cell line, 32 which indicates gingival epithelial cells might be another resource for the elevated GCF level of calprotectin in DM‐P patients.…”
Section: Discussionmentioning
confidence: 99%